2012
DOI: 10.1590/s0100-40422012000600019
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic derivatives and other chemical compounds from Cochlospermum regium

Abstract: This study describes the chemical investigation of the ethyl acetate fraction obtained from the hydroethanolic extract of the xylopodium of Cochlospermum regium (Mart. & Schr.) Pilger, which has been associated with antimicrobial activity. Phytochemical investigation produced seven phenol derivatives: ellagic acid, gallic acid, dihydrokaempferol, dihydrokaempferol-3-O-β-glucopyranoside, dihydrokaempferol-3-O-β-(6"-galloyl)-glucopyranoside, pinoresinol, and excelsin. It also contained two triacylbenze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 5 publications
(11 reference statements)
1
20
0
9
Order By: Relevance
“…Researchers have already isolated and identified several substances in Cochlospermum regium roots, e.g., dihydrokaempherol-3-O-β-glucopyranoside (Lima, Castro, Mello, Siqueira, & Kassab, 1996;Sólon et al, 2012), β-selinene, (Honda, Brum, Hess, Cruz, & Moretto, 1997), ellagic acid, gallic acid, dihydrokaempherol, dihydrokaempherol-3-O-β-(6"-galloyl)-glucopyranoside, pinoresinol, excelsine, Acta Scientiarum. Agronomy Maringá, v. 38, n. 4, p. 467-473, Oct.-Dec., 2016…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have already isolated and identified several substances in Cochlospermum regium roots, e.g., dihydrokaempherol-3-O-β-glucopyranoside (Lima, Castro, Mello, Siqueira, & Kassab, 1996;Sólon et al, 2012), β-selinene, (Honda, Brum, Hess, Cruz, & Moretto, 1997), ellagic acid, gallic acid, dihydrokaempherol, dihydrokaempherol-3-O-β-(6"-galloyl)-glucopyranoside, pinoresinol, excelsine, Acta Scientiarum. Agronomy Maringá, v. 38, n. 4, p. 467-473, Oct.-Dec., 2016…”
Section: Introductionmentioning
confidence: 99%
“…and the triacylbenzenes cochlospermines A and B (Sólon et al, 2012). However, the compound or compounds that underlie the antimicrobial activity described in ethnopharmacological reviews remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The infusion of C. regium roots has been used to treat intestinal, ovarian and uterine inflammation, dermatitis (Pio Corrêa, 1975), ulcers and rheumatoid arthritis (Lewis and Hanson, 1991;Ritto, 1996), being also reported the antimicrobial activity of its hydroethanolic extract and fractions against Staphylococcus aureus and Pseudomonas aeruginosa (Solon et al, 2012). The total aqueous extract of C. tinctorium demonstrated potent antiplasmodial activity (Traoré et al, 2006) and its rhizomes extract revealed hepatoprotective activity in aflatoxin B1 (Dalvi and Sere, 1988) and carbon tetrachloride (CC1 4 ) treated rats, and in primary rat hepatocyte cultures exposed to cytotoxic concentrations of galactosamine or CC1 4 (Diallo and Vanhaelen, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…According to some reports, the therapeutic purposes of Cochlospermum genus species (mainly hepatoprotective effects) can be explained by the presence of phytochemicals, specially phenolic an polyphenolic compounds, with gallic and ellagic acids and its derivatives as the major compounds (Diallo and Vanhaelen, 1987;Diallo et al, 1992;Solon et al, 2012;Ferreres et al, 2013). In particular, C. tinctorium revealed gallic and ellagic acids, ellegitannins and flavonoids (Diallo and Vanhaelen, 1987;Diallo et al, 1992), while C. regium showed ellagic and gallic acids, dihydrokaempferol,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation